Genetic variability of wheat (Triticurtl aestivrrnz) lines for grain yield and component characters grown under sodic and water logged conditions - SINGH, K N; KULSHRESHTHA, NEERAJ; KUMAR, VINOD; SETTER, TIM (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conductcd during 2002-04 to study genetic variability, heritability, genetic advance and interrelation estimates for 10 attributes in wheat ((Piticutil i stil’lit1L7. emend. Fiori & Paol) under waterlogged reclaimed soils. High value of phenotypic coefficient of variabiilty, genotypic coefficient of variabile lty heritabiiity and genetic advance indicated scope for improvement in biomass/m, rain yielding, tillers/m, plant height and grainslcar through selection. Significant correlarion between grain yield and days to maturity, plant height, ear length, spikoletsiear, tillersim, grailliear and biomasslrn under normal and with spikeletsicar, tiliers/m and biomas/im under waterloggcd indicated scope for improving grain yield through simoultanous selection. Path analysis further supported and highlighted the importance of biomassim, plant height, spikelets/ear, days to heading and days to maturity under drained conditions and biomass/m, spikelets/ear and days to maturity under waterlogging conditions.